An in vitro evaluation of ice apple water, Aloe vera, and propolis as a storage medium to preserve viability of human periodontal ligament fibroblasts - Samhita Bijlani; Raghavendra Shanbhog; Brinda Suhas Godhi; Priyanka Talwade; H M Tippeswamy (Wolters Kluwer Medknow Publications, 2022)
Background: A number of media that create the best possible conditions to maintain periodontal ligament (PDL) cell viability after dental avulsion have been reported. Aim: The aim of this study is to evaluate ice apple water (IAW), Aloe vera, and propolis as a storage medium to preserve the viability of human PDL fibroblasts. Methods: An in vitro comparative type of study was performed on a PDL cell culture model. PDL fibroblasts obtained from the roots of healthy premolars were cultured in Dulbecco's Modified Eagle's Medium (DMEM) and treated with ice apple water (IAW), 7% propolis extract (PE), 30% Aloe vera extract (AVE), positive control DMEM supplemented with fetal bovine serum, negative control (NC) without any agent, and incubated at 37°C for 1 h, 3 h, and 24 h. Cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay after every test period. Optical density was measured at a wavelength of 490 nm. Statistical Analysis Used: The effects of the test storage media were evaluated by one-way analysis of variance test, followed by post hoc Tukey's multiple comparison test (P < 0.05). Results: Seven percent PE demonstrated the highest capacity of maintaining PDL cell viability at 1 h and 24 h. IAW showed a statistically significantly lower percentage of viable cells at all three test periods as compared to 7% PE. After 3 h, 30% AVE demonstrated maximum viable cells. Conclusions: Within the limitations of this study, propolis at a concentration of 7% was the most effective medium for maintaining PDL cell viability.